ANALISIS TEGANGAN CIRCUMFERENSIAL DAN RADIAL BALOK PADA JEMBATAN PELENGKUNG ( STUDI KASUS JEMBATAN S.PANGKEP ) - Jaya Putra, Eddy
This thesis is an analysis study of stresses on arch bridge structure for circumferential or radial direction. The analyzed stresses are function of an arch radius, hence ease in detecting stress that occurred on the section along the arch structure. The Analysis is focused on arch beam section ratio that gives proportional stress. Besides, an analysis on how far the influence of concrete quality (re) variation has been carried out to section ratio. In this case, the variation of concrete quality should consider the construction possibility on field that has to be carried out manually without using ready mix concrete. The result of internal forces analysis shows that the arch beam structure is a compression dominated structure. And also along the structure, the stresses are dominates by those of circumferential direction.